More Than an Instrument: Improvising with failing playback media. Issue 1 (April 2021) - Higgins, Jonathan
Abstract : The adoption of playback media – such as vinyl and the compact disc – by performers as a means of sound creation and manipulation sees our perception of these media 'elevated' to the status of an instrument. As this practice develops, improvisers push these devices further in pursuit of new sounds, including actively exploring the sonic potential of failure and destruction. This article argues that when pushed to the point of failure, playback media begin to function as an improviser, exhibiting musical agency over the performance that mirrors that of human improvisers. This article will identify how failing playback functions within a performance, and explore the ways in which it can be understood to improvise, discussing how failing playback media can engage in a dialogical back and forth with human improvisers as well as the ways it can directly influence and determine the structure and musical content of a performance.